A DEIXIS ANALYSIS OF SONG LYRICS IN DAVID ARCULETHA ALBUM - EKASARI, PRIMA (2010)
This research paper studies one of elements to form a discourse of song in David Archuleta Album. The researcher chooses this topic because many of people are interested in this album, especially from woman teenagers. The data are taken from David Archuleta Album. The objectives of this research are 1) to find the kinds of deixis from the data of song and 2) to describe the meaning of kinds of deixis from the data. In gathering the data the researcher uses the documentation method. The data are taken from song lyrics in David Archuleta Album. The first, to analyze the kinds of deixis, the researcher uses deixis analysis. The second, to analyze the meaning of deixis, the researcher refers to contexts analysis. The results of this research paper show that there are three kinds of deixis; person deixis, place deixis and time deixis. The meaning, the researcher found 1) person deixis, the word I in this song refers to the singer. The word you refer to the girl, the word we refers to singer and girl, the word me in this song refers to the singer. 2) Place deixis, the word there refers to locations that close with speaker; it is in the sea, the word here is place that the writer has looked the beautiful moon at night. When he thinking his girl and 3) time deixis; the word now refers to time of speaking. The word tonight refers to the time when singer feels something.